Performance Evaluation Of 3d Printed Hip Protectors - Yahaya, Suleiman Abimbola (2021)
Fall to the sideways is a significant threat to the aged population with potentially severe hip fracture implications. Hence, being the most effective strategy for avoiding hip fractures among the vulnerable population, there is a need to ensure hip protectors are properly evaluated, cost-effective, and customized to the hip shape to improve adherence. This study aims to evaluate the feasibility of a proposed 3D printed hip protecting pad for biomechanical fracture prevention in sideways fall and undertakes strategies to improve such printed hip protectors’ performance. It is hypothesized that this technique would be both feasible and mechanically effective. Therefore, a biomechanical impact tower incorporated with a surrogate anatomical proximal femoral and hip-shaped surrogate soft tissue was developed to access the impact attenuation capability of hip protectors in simulated sideways fall. A custom-fit three-dimensional (3D) printed hip protector was designed from an actual hip profile geometry imposed on the surface of a 3D modeled hip shield. It was printed by stereolithographic (SLA) printing method using verowhite copolymer resin and subsequently optimized by response surface methodology using four types of thermoplastic polyurethane (TPU 75%, 85%, 95%, 98%) shore A hardness, varied infill density (25%, 50%, 75% and 100%) and different shell thickness (0.86 mm, 1.29mm and 1.72mm) printed using fuse deposition modeling (FDM). Also, the flexibility and compressive strength of the various configurations of the hip protectors were investigated. Lastly, a support vector regression model was developed to predict the impact attenuation capability of the hip protectors at different energy levels. The results demonstrated that the force transmitted to the femoral neck was below the average fracture threshold of older adults (3472 N) using the 3D Printed SLA hip protector, and it competes favorably with an existing hip protector. Furthermore, the ability to manipulate the infill density has the most significant influence on the impact attenuation properties, followed by the infill density combined with the material shore hardness. Also, Good agreement was found between the model results and test results. The applied model’s precision and accuracy show its applicability in predicting a hip protector design’s optimum impact attenuation capacity. Conclusively, by maximizing all the parameters, it is demonstrated that using an additive manufacturing technique to print hip protectors could be an effective strategy in improving the performance of the pad and curbing hip fractures. The effectiveness and acceptability of this newly designed hip protector for older adults can be assessed further by conducting future clinical trials.